Association between underlying disease and serious events on a world cruise ship: A prospective cohort study. Issue 41 (May 2021) - Aoki, Yoshihiro; Amaya Dimas, Liliana del Carmen; Hatachi, Takeshi; Kawamura, Atsushi; Suganuma, Kazuki; Shiroto, Kosuke; Miyauchi, Naoto; Shibata, Shunichi; Matsubara, Chitose; Yoshiike, Shouichi; Koyama, Toru
Abstract: Background: This study aimed to clarify the effects of underlying diseases on clinical outcomes of patients aboard a world cruise ship. Methods: This prospective cohort study included patients who sought physician consultations at an onboard clinic on a 105-day world cruise (September–December 201X) on a ship chartered by a Japanese travel agency. Multivariable logistic regression analysis was performed to ascertain whether any concurrent disease, such as hypertension, was associated with additional onboard treatment by the primary physician or serious events, including unexpected final disembarkation, temporary disembarkation for hospitalization ashore, shore-side referral, and onboard clinic admission. Results: Of 313 patients, 182 (58%) had at least one underlying disease. Sixty-eight (22%) required additional treatment, and 24 (8%) experienced serious events. After adjusting for age, sex, and underlying diseases, the 60–69- and 70–74-year age groups had a lower risk of serious events than the ≤59-year age group (odds ratio [OR], 95% confidence interval [CI]: 0.24, 0.069–0.81; p = 0.022 and 0.045, 0.0051–0.47; p = 0.0055). Underlying disease was associated with serious events (OR, 95% CI: 3.2, 1.1–9.5; p = 0.036). Conclusions: Unexpected events can occur in patients on world cruises regardless of age. Preexisting diseases may confer higher risk of serious events. Highlights: Serious events requiring additional treatments can occur on world cruises. Underlying diseases may increase the risk of serious events onboard. Older age, in itself, was unassociated with an increased risk of serious events.